Knowledge Management (Km) Information System for Laguna State Polytechnic University - Santa Cruz Campus (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Documents in any institution have been outnumbered and scattered in various repositories, hindering efficient information retrieval and threatening institutional memory. This study developed a web-based Knowledge Management Information System for Laguna State Polytechnic University - Sta. Cruz Campus that consolidates core institutional documents such as research outputs, policies, course materials and extension documents into a centralized, secure, and searchable platform. Employing a Developmental and Experimental Research Design, KMIS engineered four core intelligent components: Role-Based Access Control centralized repository, Retrieval Augmented Generation pipeline that uses vector embeddings to utilize semantic search and LLM-generated summaries from natural language queries. Lastly, the automated QPRO analysis engine. The developed KRA text classification model achieved an overall accuracy of 98% and automatically categorized institutional reports against the 22 Key Result Areas from the 2025-2029 LSPU Strategic Plan.